Strategic Communication and Performance of Universities in Kenya - Mohamed, Zamzam; Ngugi, Karanja; Deya, Jared (Human Resource and Leadership Journal, 2026)
Purpose: This thesis endeavored to explore on the relationship between strategic communication and performance of universities in Kenya. The thesis study anchored the systems theory of communication. Methodology: The study used descriptive research design. The target population for this study were all the 64 respondents from chartered universities in Kenya. A structured and semi–structured questionnaire was used for primary data collection. The questionnaire was pilot tested to verify validity and reliability of the instruments. The pilot study comprised of ten percent (10%) of equivalent of study respondents amounting to 27 respondents. Secondary data was collected from journals, books, internet searches and articles through desk research from each university. Collected data was coded, organized and analyzed by Statistical Package for Social Sciences Version 28. Descriptive statistics such as mean and standard deviation was used to analyze the data. Correlation and regression analysis was conducted to find the relationship between the independent and dependent variable. The results is presented in tables, graphs and histograms. The overall Cronbach Alpha value for reliability was over 0.7 and Content validity of over 0.5 respectively. The seven types of validity tests were also carried out; such; Content validity, face validity, construct validity etc. Findings: The study in summary and conclusion indicated that strategic communication had a significant statistical effect on the performance of universities in Kenya. Unique Contribution to Theory, Policy and Practice: This study advances theory by applying systems theory to Kenyan universities, showing how strategic communication shapes organizational performance. For policy, it provides evidence for administrators and regulators to strengthen communication channels, enhancing institutional effectiveness. Practically, it offers university leaders actionable guidance for designing communication strategies that improve stakeholder engagement, decision-making, and overall performance.